Public Relations Panacea for Mental Health-Care Delivery: Study of Federal Neuro-Psychiatric Hospital Yaba, Lagos - Ivwighren , Hannah Emuobosa; Ochonogor, Christopher I.; Joloko , Efemena Odharigho (PERSPEKTIF, 2024)
This mixed-methods study investigates the role of public relations in enhancing mental healthcare delivery at Federal Neuro-Psychiatric Hospital Yaba, Lagos. The study examines a sample of 400 respondents through interviews, surveys, and document analysed to explore the implementation and impact of public relations initiatives. Document analysis examines the strategies and out-of-public relations campaigns at the hospital. Findings highlight the critical role of public relations in changing negative perceptions, promoting inclusivity, and fostering understanding. The study shows that public relations initiatives, and communication techniques, including media campaigns and community outreach programs, can foster a positive perception of mental healthcare, disseminate essential information, advocate for increased support, and bridge the gap of limited public awareness about mental health resources and services. The study's findings contribute to knowledge on the role of public relations in mental health and provide insights for policymakers, healthcare professionals, and public relations practitioners seeking to improve mental healthcare services. The research underscores the importance of ongoing efforts to address challenges in the mental health sector.This mixed-methods study investigated the role of public relations in improving mental health services at Yaba Federal Psychiatric Hospital, Lagos. Using interviews, surveys, and document analysis, the study investigated a sample of 400 respondents to explore the implementation and impact of public relations initiatives. In particular, document analysis examined the strategies and campaigns undertaken by the hospital. The findings underscore the critical role of public relations in reshaping negative perceptions, fostering inclusivity, and nurturing understanding. In addition, the study revealed that public relations initiatives, coupled with communication techniques such as media campaigns and community outreach programs, can foster positive perceptions of mental health services, facilitate the dissemination of important information, advocate for increased support, and bridge the gap between limited public awareness of mental health resources and services. This research offers insights for policy makers, health professionals, and public relations practitioners seeking to improve mental health services. In addition, this study emphasizes the need for continued efforts to address the challenges faced in the mental health sector, including a clearer delineation of research boundaries and a deeper exploration of the barriers faced in implementing public relations initiatives in hospital settings.